Comparison of naphthalene removal performance using H2O2, sodium percarbonate and calcium peroxide oxidants activated by ferrous ions and degradation mechanism. (November 2021) - Yang, Rumin; Zeng, Guilu; Xu, Zhiqiang; Zhou, Zhengyuan; Huang, Jingyao; Fu, Rongbing; Lyu, Shuguang
Abstract: The presence of polycyclic aromatic hydrocarbons (PAHs) in groundwater is making a great threat to human health in the world which has received an increasing environmental concern. Among various Fenton oxidation processes, 97.6%, 92.1% and 89.4% naphthalene (NaP) removals were observed using hydrogen peroxide (H2 O2 ), sodium percarbonate (SPC) and calcium peroxide (CP) as oxidants activated by Fe(II) in ultrapure water tests, respectively. While, the inhibitory effect on NaP degradation caused by the weak alkaline solution pH and the presence of HCO3 − in actual groundwater could be compensated by doubling dosages of oxidants and Fe(II) to different extent. 98.0%, 49.8% and 11.5% of NaP were degraded by using H2 O2, SPC and CP, respectively, strongly suggesting the best H2 O2 performance among them. It was observed that 83.3% and 9.6% inhibition on NaP degradation in H2 O2 /Fe(II)/NaP system occurred in the presence of isopropyl alcohol and chloroform, confirming that both hydroxyl radical (HO) and superoxide anion radical ( ) contributed to NaP degradation in Fenton process and HO was the prominent radical. The presence of HO was further demonstrated by electro-spin resonance spectrometer analysis. The identification of transformation products of NaP revealed that hydroxylation and ring rupture were the main NaP degradation pathways. Graphical abstract: Image 1 Highlights: H2 O2 performed best among H2 O2, SPC and CP for NaP degradation. HO was the dominant ROSs in H2 O2 (SPC or CP)/Fe(II)/NaP system. HCO3 — had significant inhibitory influence on NaP degradation. Hydroxylation and ring rupture were the main NaP degradation pathways.